Life course perspective for improving oral health: strategies and interventions to integrate oral health care and primary health care in community health centers - Northridge, Mary E.; Lieberman, Martin (Frontiers in Oral Health, 2025)
In the United States, disparities in access to quality oral health care exist at every stage across the life course. The net result is a greater likelihood of poor oral health at every age for people who live in underserved and rural communities than for people who live in communities with better access to quality oral health care. Both universal and targeted interventions at multiple levels of influence across the life course and intergenerationally are needed to eliminate disparities in access to oral health care and end the disgrace of poor oral health as the US national symbol of social inequality. While community health centers hold promise for delivering patient-centered, value-based care, they experience challenges related to the oral health literacy of patients and organizations and to the building of sufficient capacity to meet the high demand for oral health care services. To address the training needs of the US dentistry workforce, the long-term goal of the New York University Langone Dental Medicine Postdoctoral Residency Programs is to improve oral health care access and delivery across the life course for people of all ages and intergenerationally. The short-term goal is to recruit and train dentists to lead patient-centered models of integrated care delivery at community health centers in underserved and rural communities of 30 US states, Puerto Rico, and the US Virgin Islands. This paper presents the capstone findings of a 5-year postdoctoral dental residency training project built upon a foundation of shared decision-making and motivational interviewing training for dental faculty and residents. Improving patient experience and patient-reported outcomes are critical in transforming dentistry from a fee-for-service to a value-based health care model. Scaling up promising interventions and addressing time and resource constraints in community health centers require the broad commitment of communities, organizations, patients and their families in demanding and realizing the US societal goal of oral health for all.